Peter Weir : Interviews - Tibbetts, John C. (Book collections on Project MUSE., 2014)
Peter Weir: Interviews is the first volume of interviews to be published on the esteemed Australian director. Although Weir (b. 1944) has acquired a reputation of being guarded about his life and work, these interviews by archivists, journalists, historians, and colleagues reveal him to be a most amiable and forthcoming subject.